The ethical challenge of Big Tech's "disruptive philanthropy". Issue 3 (2nd July 2020) - Manning, Paul; Baker, Nigel; Stokes, Peter
Abstract: This article provides a review of research into global philanthropy and the disruptive practices of new technology companies. In this article we detail how "Big Tech" has created a new marketization of philanthropy, based on its sectoral values of innovation, entrepreneurialism and focus on financial and performance metrics. Consequently, we argue for a new ontology of philanthropy that acknowledges marketization as its guiding principle. The study examines and compares different market-focused, philanthropic paradigms, which have evolved through the business values of Big Tech and examines their moral motivations. The topic is viewed through the lens of 'hybrid organizations'; a model for nonprofit entities and social businesses which, in turn, are seeking a market-oriented pathway of balancing the twin demands of managing mission and money. A conceptual framework is then provided to inform practitioners in nonprofit organizations about the issues and risks of engaging with the new types of philanthropy, to which we collectively refer as 'disruptive philanthropy'. The article concludes by recommending further research into the ethics of Big Tech to understand the true motivations behind its philanthropic practices at a time when the sector is under intense governmental and media scrutiny.